Pengaruh Green Finance, Struktur Modal, dan Kinerja Lingkungan Terhadap Profitabilitas Pada Perusahaan Pertambangan - Ni Wayan Indah Mahayani; Rofiqah Wahdah; Yanuar Bachtiar; Dini Rusqiati (Owner : Riset dan Jurnal Akuntansi, 2026)
This study investigates the influence of green finance, capital structure, and environmental performance on the profitability of mining sub-sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. A quantitative research approach was employed using secondary data obtained from annual reports and sustainability reports. The study population consisted of 33 companies, and purposive sampling based on predetermined criteria produced 132 firm-year observations. Data were analyzed using multiple linear regression, preceded by classical assumption tests and hypothesis testing through partial and simultaneous tests. Profitability was measured using Return on Assets (ROA), green finance was proxied by the Green Coin Rating (GCR), capital structure was measured using the Debt to Equity Ratio (DER), and environmental performance was evaluated using the Company Environmental Management Performance Assessment Program (PROPER) rating. The results indicate that green finance has a positive and significant effect on company profitability, while capital structure has a negative and significant effect. In contrast, environmental performance does not show a significant effect on profitability. Simultaneously, green finance, capital structure, and environmental performance significantly influence profitability. These findings suggest that corporate financial performance is shaped not only by financial structure but also by the adoption of sustainable financial practices, highlighting the importance of integrating financial management with sustainability strategies.